Diabetes mellitus and cardiovascular clinical characteristics of Spanish women with stable ischaemic heart disease: Data from the SIRENA study. (January 2017) - Gámez, José M.; Masmiquel, Luis; Ripoll, Tomás; Barrios, Vivencio; Anguita, Manuel; ,
Abstract: The relationship between diabetes and the cardiovascular clinical characteristics of Spanish women with stable ischaemic heart disease was studied in a nationwide cross-sectional study. Diabetes was related to a higher burden of risk factors, comorbidity, multivessel disease and coronary surgery.